Tantangan Pengangguran Sumber Daya Manusia di Era Digitalisasi: Penelitian - Achni, Oktami; Kumaidi; Mawardi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The digitalization era has brought major transformations to the world of work, where automation, artificial intelligence, and information technology have replaced many conventional human roles. This shift presents serious challenges to employment, especially for workers lacking digital skills. This article aims to analyze the main challenges of unemployment in the digitalization era, its contributing factors, and the strategies that can be implemented to address these challenges. Through literature review and secondary data analysis, it is found that digital unemployment is not only about job losses but also involves digital access inequality, outdated education curricula, and slow adaptation of labor policies. The study concludes that a cross-sectoral collaborative approach and transformation in the education system are necessary to prepare human resources that are relevant to the demands of the digital era.